(untitled) (Journal of Comparative & International Higher Education, 2022)
Despite the promise that improving campus climate offers for promoting students’ socialization and psychological safety, marginalized students continue to face negative experiences on campuses that hamper their academic success. This experience is mainly grave in graduate educational environments, the science, technology, engineering, and mathematics (STEM) fields, and at Predominantly White Institutions (PWIs). Meanwhile, foreign-born students are represented and thrive in these educational environments, despite the odds. In the United States (U.S.), foreign-born students are critical to diversity in graduate education, national innovation and economic growth, and global competitiveness in the STEM fields. Specifically, Black Sub-Saharan African-born (BSSA) students are unique; hence, there are within-group differences depicted by socio-cultural orientation among Black students. Therefore, seeking to explore the Black student population’s perspectives as a monolith is problematic. From this backdrop, this dissertation seeks to unbundle the Black experience by focusing on BSSA graduate students in STEM at PWIs.